Physiologically active hydrogel (in situ gel) of sparfloxacin and its evaluation for ocular retention using gamma scintigraphy - Himanshu Gupta; Aqil Malik; R K Khar; Asgar Ali; Aseem Bhatnagar; Gaurav Mittal (Wolters Kluwer Medknow Publications, 2015)
Objective: Due to the structure and physiological barrier of eye, only 1% of instilled dose is available for action on the corneal surface. In this work, we developed and evaluated chitosan (pH sensitive) and gellan gum (ion sensitive) in situ gel of sparfloxacin to improve precorneal residence time. Materials and Methods: A protocol for radiolabeling of sparfloxacin with Tc-99m was optimized to study the ocular retention using gamma scintigraphy technique. Results: The clear formulation was developed. In vitro release showed a sustained and prolonged release compared to plain eye drop solution. Dynamic and static gamma scintigraphy showed better retention than plain eye drops. The ocular tolerance test (hen's egg test-chorioallantoic membrane test and infra-red study) showed that the formulation is nonirritant and can be used as ocular vehicle. Conclusion: Radiolabel protocol for sparfloxacin was successfully developed and evaluated on ocular retention studies of developed in situ gel. The developed in situ gel is non irritant and can go further with clinical evaluation.